Injuries and illnesses during the 54th FIS Nordic World Ski Championships 2023 in Planica: a prospective cohort study - Kastner, T.; Dandrieux, P.-E.; Fohrmann, D.; Frohberg, F.; Turel, M.; Valtonen, M.; Edouard, P.; Spörri, J.; Wolfarth, B.; Junge, A.; Hollander, K. (BMJ Open Sport & Exercise Medicine, 2025)
Objective To describe the incidence and characteristics of injuries and illnesses that occurred during the 54th Nordic World Ski Championships in Planica (Slovenia) 2023, including the disciplines of cross-country skiing, Nordic combined and ski jumping.